Pengaruh Budaya Sekolah, Kepuasan Kerja dan Motivasi Berprestasi Terhadap Kinerja Guru di Sekolah Penggerak Jenjang SMP Kabupaten Bireuen - Osey Putri Salehha; Iis Marsithah; Sari Rizki (Departement of Mathematics Education, 2024)
The low quality of education in Indonesia hinders the nation's progress. UNESCO and PISA reports show that Indonesia lags significantly in terms of education and teacher quality. To address this issue, the government has introduced the independent curriculum and the sekolah penggerak. This study aims to analyze the influence of school culture, job satisfaction, and achievement motivation on teacher performance in the Driving School Program at the junior high school level in Bireuen Regency. This quantitative research uses an associative method with a sample of 152 teachers from a population of 246, selected through proportionate stratified random sampling. Data testing includes normality, linearity, multicollinearity, and heteroscedasticity tests, using simple linear regression analysis and Moderated Regression Analysis (MRA). The results show that school culture has a positive and significant effect on teacher performance (t-value 10.079, Sig 0.000). However, job satisfaction (t-value -1.453, Sig 0.148) and achievement motivation (t-value -1.560, Sig 0.287) do not moderate this effect. These findings are crucial for educational policy to focus on strengthening school culture to improve teacher performance. Additionally, programs to enhance job satisfaction and achievement motivation are still necessary to support overall teacher performance.